COMPARATIVE EFFICACY OF ANTIPROGESTIN AND DOPAMINE AGONIST IN THE TREATMENT OF CANINE PYOMETRA - SINGH, L. KIPJEN; PATRA, M K; MISHRA, G K; LINDA, N; SAXENA, A C; DE, U K; KUMAR, H; NARAYANAN, K (The Indian Journal of Animal Reproduction, 2020)
The study was designed to investigate the comparative efficacy of antiprogestin vis-à-vis dopamine agonist inthe treatment of pyometra in bitches (n=16) presented to the Referral Veterinary Polyclinic - Teaching VeterinaryClinical Complex, Indian Veterinary Research Institute, Izatnagar. Pyometra was confirmed by presumptive clinicalsigns and transabdominal ultrasonography and the positive bitches were randomly subjected to two treatment regime,T1 (Mifepristone @ 2.5mg/kg p.o. on day 0, 1 and 10) and T2 (dopamine agonist, Cabergoline @ 5μg/kg, p.o. for 7days), n=8/group. Cloprostenol @5μg/kg, s/c on alternate days for 7 days was included in both the groups along withempirical fluid and antibiotics. The treatment responses was determined by general clinical examination, changes ofblood urea nitrogen, serum creatinine, prostaglandin F metabolites (PGFM) and progesterone (P4) level at pre-treatmentand 10 days post-treatment. Recurrence or recovery was recorded on follow up examination and telephonic feedbackafter 100 days post treatment. A reduction in BUN and P4 concentration was recorded in both the treatment groups.The non-recurrence rate (%) of pyometra in the mifepristone treated bitches was 85.7 percent compared to 51.43percent in cabergoline (P=0.09) treatment. From this study it can be concluded that addition of mifepristone improvedthe recovery rate with a reduction of recurrence rate in the medically treated pyometra cases in bitch.
Keywords: Pyometra; Mifepristone; PGFM; P4; Canine